Polarized pasts : heritage and belonging in times of political polarization - Niklasson, Elisabeth (New York : Berghahn Books, 2023)
"When questions of belonging enter the forefront of political debates, so too does heritage. From different ends at the political spectrum, people invoke the past to validate their stance on immigration, equality and security. In the wake of European crises and a polarized US political landscape, heritage is invoked to both halt and embrace immigration, as well as to resist and further globalization. Essays demonstrate how ancient monuments and sites, bygone eras and political regimes, even your genetic ancestry, can become wrapped up in polarized political debates. Together, the texts pave the way for a better understanding of the role of the heritage in society"--
Heritage and belonging in times of political polarization / Elisabeth Niklasson -- Heritage, memory, race : the culture of the far right / Chiara de Cesari -- Innocence reinvented : far-right myth-making in Hungary / Cathrine Thorleifsson -- Possessive pasts : heritage in far-right rhetoric in Scandinavia / Elisabeth Niklasson and Herdis Hølleland -- 'Western civilization', white supremacism and the myth of a white ancient Greece / Rebecca Futo Kennedy -- Memory between repression and deception : Germany's shattered stratigraphies / Reinhard Bernbeck -- Walking through the darkest valley : heritage and hatred in the era of reactionary populism / Alfredo González-Ruibal -- Is DNA a dangerous heritage? / Chip Colwell -- The sigtuna debacle : a story of ancient DNA, immigrants and fake news in a Viking age town in Sweden / Anna Källén -- The threat of essence : reflections on the heritage of racism and the racism of heritage / Michael Herzfeld.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on December 20, 2022).
JSTOR
Keywords: Polarization (Social sciences); National characteristics -- Political aspects; Cultural property -- Political aspects; Ethnicity -- Political aspects; Right and left (Political science); Emigration and immigration -- Political aspects; Polarisation collective; Caractéristiques nationales -- Aspect politique; Ethnicité -- Aspect politique; Patrimoine culturel immatériel -- Aspect politique; SOCIAL SCIENCE / Anthropology / Cultural & Social; Emigration and immigration -- Political aspects; Ethnicity -- Political aspects; National characteristics -- Political aspects; Polarization (Social sciences); Right and left (Political science); Electronic books